2020
DOI: 10.1007/s10834-020-09681-0
|View full text |Cite
|
Sign up to set email alerts
|

How Do Economic Shocks Affect Family Health Care Spending Burdens?

Abstract: This research was funded by a grant from the Agency for Healthcare Research and Quality (AHRQ R01HS024053). We thank Samuel Zuvekas and Steven Hill of AHRQ for their expert advice on the use of MEPS data and development of longitudinal family weights. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research.NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…Enormous medical expenses resulting from health impacts impose a heavy economic burden on families, severely limiting their wealth and leading them to prioritize current consumption. In the short term, it directly leads to the loss of patients' labor capacity and the loss or deprivation of time for family members to participate in production activities due to care responsibilities, thereby negatively affecting household or individual labor income (K. Alam & Mahal, 2014; Grafova et al, 2020; Y. J. Wang et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Enormous medical expenses resulting from health impacts impose a heavy economic burden on families, severely limiting their wealth and leading them to prioritize current consumption. In the short term, it directly leads to the loss of patients' labor capacity and the loss or deprivation of time for family members to participate in production activities due to care responsibilities, thereby negatively affecting household or individual labor income (K. Alam & Mahal, 2014; Grafova et al, 2020; Y. J. Wang et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, those studies have analysed the relationship during periods of financial stability. There is hardly any empirical evidence on how household expenditure behaves during periods of financial crisis, although it has been widely acknowledged that such periods exert considerably adverse effects on pensions, as income sources, as well as the way they are spent (Grafova et al, 2020;Impavido & Tower, 2009). In this paper, we examined how expenditure behaves at retirement during turbulent times using household-level data, and examined the role of pension cuts during a severe financial crisis in explaining the drop in expenditures at retirement.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the heat waves in France have caused more excess mortality and years-of-life loss, and the population has experienced restricted activity [2]. In addition, the relationship between economic development and residents' health has been detected [3][4][5][6]. Considering the influence of opening-up on residents' health, it has been confirmed that the impact of foreign direct investment could have a negative impact on residents' health, especially in the most developed countries [7].…”
Section: Introductionmentioning
confidence: 99%